2004
DOI: 10.1080/1369378032000141417
|View full text |Cite
|
Sign up to set email alerts
|

Canine paracoccidioidomycosis

Abstract: Paracoccidioidomycosis (PCM) is a severe disease caused by the dimorphic fungus Paracoccidioides brasiliensis, which is characterized by granulomatous pulmonary and systemic lesions, affecting mainly men between 20 and 60 years of age. Reports of PCM disease in animals are rare, but the disease has been described in armadillos. On the other hand, PCM infection of domestic and wild animals detected by serological or cutaneous tests in the absence of apparent disease has been frequently reported. We present here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 10 publications
0
34
0
14
Order By: Relevance
“…Specific P. brasiliensis DNA amplicons were detected in samples of mesenteric lymph node, spleen, lung, adrenal glands, and kidney of Cavia aperea (''guinea pig''), in lung and liver of Sphiggurus spinosus (''porcupine''), in lungs of Gallictis vittata (''grison'') and Procyon cancrivoros (''raccoon''), as well as in several organs of the nine-and seven-banded armadillos (Dasypus septemcinctus), thus indicating that in endemic areas P. brasiliensis infection in wild animals, exhibiting a certain systemic dissemination, might be more common than initially supposed. In fact, intradermal tests have also indicated that several wild and domestic animals could be infected by the fungus [72], and PCM disease was recently confirmed to occur in dogs [73,74].…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencementioning
confidence: 99%
“…Specific P. brasiliensis DNA amplicons were detected in samples of mesenteric lymph node, spleen, lung, adrenal glands, and kidney of Cavia aperea (''guinea pig''), in lung and liver of Sphiggurus spinosus (''porcupine''), in lungs of Gallictis vittata (''grison'') and Procyon cancrivoros (''raccoon''), as well as in several organs of the nine-and seven-banded armadillos (Dasypus septemcinctus), thus indicating that in endemic areas P. brasiliensis infection in wild animals, exhibiting a certain systemic dissemination, might be more common than initially supposed. In fact, intradermal tests have also indicated that several wild and domestic animals could be infected by the fungus [72], and PCM disease was recently confirmed to occur in dogs [73,74].…”
Section: Origin and Maintenance Of P Brasiliensis' Virulencementioning
confidence: 99%
“…The study showed positivity rates ranging from 14.5 % to 89.5 %, using the ELISA technique [19]. In addition, in 2004, the first confirmed case of paracoccidioidomycosis in a dog with a strictly urban life was reported [20].…”
Section: Epidemiologymentioning
confidence: 98%
“…Fagundes et al (2002) encontraram uma positividade de 26,5% em estudo soroepidemiológico com 275 cães de áreas rurais da região de Botucatu (SP), utilizando ELISA com exoantígeno de P. brasiliensis. Ricci et al (2004) relataram o primeiro caso de PCM-doença em cão. O animal apresentou aumento dos linfonodos cervicais e a confirmação da doença foi feita por meio de exames histopatológico, de imunohistoquímica e de biologia molecular (PCR) embora não tenha ocorrido isolamento do fungo.…”
Section: Paracoccidioidomicose Em Cãesunclassified